Immunological considerations regarding parental concerns on pediatric immunizations. Issue 23 (25th May 2017) - Nicoli, Francesco; Appay, Victor
Abstract: Despite the fundamental role of vaccines in the decline of infant mortality, parents may decide to decline vaccination for their own children. Many factors may influence this decision, such as the belief that the infant immune system is weakened by vaccines, and concerns have been raised about the number of vaccines and the early age at which they are administered. Studies focused on the infant immune system and its reaction to immunizations, summarized in this review, show that vaccines can overcome those suboptimal features of infant immune system that render them more at risk of infections and of their severe manifestations. In addition, many vaccines have been shown to improve heterologous innate and adaptive immunity resulting in lower mortality rates for fully vaccinated children. Thus, multiple vaccinations are necessary and not dangerous, as infants can respond to several antigens as well as when responding to single stimuli. Current immunization schedules have been developed and tested to avoid vaccine interference, improve benefits and reduce side effects compared to single administrations. The infant immune system is therefore capable, early after birth, of managing several antigenic challenges and exploits them to prompt its development.